1994
DOI: 10.3168/jds.s0022-0302(94)77094-6
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Variation of Test Day Milk Yield, Somatic Cell Count, Fat, and Protein in Dairy Sheep

Abstract: Between January and July 1992, 8403 monthly test day records were obtained from 3202 ewes from 22 Churra dairy flocks in the Castilla-León region of Spain. Variables measured were milk yield, SCC, and fat and protein percentages; means were 912 ml, 1501 x 10(3) cells/ml, 6.76%, and 6.28%. Analysis of variance showed significant effects of flock, stage of lactation, parity, and type of birth on milk yield, SCC, and composition. Variability in SCC among flocks was high and ranged from 420 to 2719 x 10(3) cells/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
42
2
34

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(98 citation statements)
references
References 20 publications
20
42
2
34
Order By: Relevance
“…The stage of lactation had a highly significant effect on all milk components, however only the contents of TS, SNF, F, P and CN increased gradually with the advancement of lactation. The above-mentioned tendency concerning the contents of TS, SNF, F and P is in line with the results published by Casoli et al (1989), Gonzalo et al (1994), Čapistrák et al (1995), Fuertes et al (1998) and Ploumi et al (1998). However, Jelínek et al (1990) and Hassan (1995) reported that during the first 2-5 weeks of lactation the contents of the above-mentioned components decreased as a result of the increased DMY in this period.…”
Section: Resultssupporting
confidence: 88%
“…The stage of lactation had a highly significant effect on all milk components, however only the contents of TS, SNF, F, P and CN increased gradually with the advancement of lactation. The above-mentioned tendency concerning the contents of TS, SNF, F and P is in line with the results published by Casoli et al (1989), Gonzalo et al (1994), Čapistrák et al (1995), Fuertes et al (1998) and Ploumi et al (1998). However, Jelínek et al (1990) and Hassan (1995) reported that during the first 2-5 weeks of lactation the contents of the above-mentioned components decreased as a result of the increased DMY in this period.…”
Section: Resultssupporting
confidence: 88%
“…Of these chemical parameters lactose was the most constant, con®rming its role as an osmotic regulator and a compensator for variations in all the other components (Bertoni, 1996). The average values for the fat and protein contents were consistent with those found in other dairy sheep breeds (Flamant and Casu, 1977;Barillet and Boichard, 1987;Sakul and Boylan, 1992;Gonzalo et al, 1994;Cappio-Borlino et al, 1997) and in the Massese breed (Casoli et al, 1989). Values for pH exhibited only moderate variation but all renneting parameters had a high CV at about 50%.…”
Section: Methodssupporting
confidence: 86%
“…The breed itself is a factor in milk composition (Barillet, 1985;Sakul and Boylan, 1992) but within breeds the most signi®cant compositional variations are determined by the stage of lactation as shown by Casoli et al (1989), Marõ Áa andGabin Äa (1993), Delacroix-Buchet et al (1994), Gonzalo et al (1994), Carta et al (1995), Hassan (1995) and Cappio-Borlino et al (1997). Sheep have, moreover, a particular reproductive rhythm relating to individual breeds and to external factors of climate and breeding environment, and the seasonality of lambing, which is common to several breeds, often prevents the effects of stage of lactation, season, and nutrition from being distinguished separately (Pellegrini et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Studies analyzing the factors affecting ewe's milk yield and milk composition (Margetín et Antonič et al, 2013) such as breed, age at lambing, parity, litter size as well as studies estimating lactation curves (Oravcová et al, 2006(Oravcová et al, , 2007 were performed. Among factors that affect variation of daily milk yield, milk fat and protein content, the effect of stage of lactation was reported important by Gonzalo et al (1994), Pavic et al (2002), Komprej et al (2012). Various lactation curves based on Wood (1967), Cobby and Le Du (1978), Wilmink (1987) model were firstly used in cattle.…”
mentioning
confidence: 99%